The Analysis of Students’ Errors in Pronouncing English Consonant Sounds in Reading Aloud - Fitri, Mainar; Fauziah, Miftahul; Nurzena, Nurzena; Mirawati, Mirawati (Universitas Pahlawan Tuanku Tambusai, 2025)
EFL learners often make errors in pronouncing English consonant sounds either in speaking or in reading aloud. Most previous studies researched on students’ errors in pronouncing English sounds in speaking and reading aloud. However, a few studies were conducted on analyzing students’ errors in pronouncing consonant sounds in reading aloud. So, this research aimed to describe the most dominant error made by the students in pronouncing English consonant sounds at a state senior high school in Pekanbaru, Indonesia. The research design used was descriprive quantitative. The instrument used was an oral test. The result showed that the most dominant error made by the students in pronouncing consonant sounds was dental sound “th” [θ] with the percentage of errors 91%. It can be concluded that most of the students make errors in pronouncing dental sounds “th” [θ].